Single nucleotide polymorphisms in desaturases genes – effect on docosahexaenoic acid levels in maternal and fetal tissues and early development of the child. - Malinowska, Malwina Anna; Wiśniewski, Oskar Wojciech; Warchoł, Magdalena (Journal of Medical Science, 2017)
Polyunsaturated fatty acids (PUFAs) beneficially affect an optimal fetal growth and development right after birth. This effect is particularly significant for the growth and maturation of brain. Therefore, an appropriate maternal regimens for PUFAs supplementation, during pregnancy and lactation, may influence birth outcome and infant health. Recently, it has been shown that genetic profile is an another factor determining long-chain polyunsaturated fatty acids (LC-PUFA) composition in human tissues. Single Nucleotide Polymorphisms (SNPs) in the fatty desaturase 1 and 2 (FADS1 and FADS2) modify endogenous synthesis of PUFAs indicating that PUFAs blood concentration may depend on genetic background. What is more, a number of studies indicate that maternal FADS gene variants by their influence on LC-PUFAs synthesis are associated with child’s health right after birth as well as within first years of life. Determining individual dietary recommendations for clinical practice can be beneficial for both mother and the child.